Targeted ultra‐performance liquid chromatography/tandem mass spectrometric quantification of methylated amines and selected amino acids in biofluids. (20th February 2020) - Roggensack, Tim; Merz, Benedikt; Dick, Niels; Bub, Achim; Krüger, Ralf
Abstract : Rationale: Methylated amino compounds and basic amino acids are important analyte classes with high relevance in nutrition, physical activity and physiology. Reliable and easy quantification methods covering a variety of metabolites in body fluids are a prerequisite for efficient investigations in the field of food and nutrition. Methods: Targeted ultra‐performance liquid chromatography/tandem mass spectrometric (UHPLC/MS) analysis was performed using HILIC separation and timed ESI‐MRM detection, combined with a short sample preparation. Calibration in urine and blood plasma was achieved by matrix‐matched standards, isotope‐labelled internal standards and standard addition. The method was fully validated and the performance was evaluated using a subset from the Karlsruhe Metabolomics and Nutrition (KarMeN) study. Results: Within this method, a total of 30 compounds could be quantified simultaneously in a short run of 9 min in both body fluids. This covers a variety of free amino compounds which are present in very different concentrations. The method is easy, precise and robust, and has a broad working range. As a proof of principle, literature‐based associations of certain metabolites with dietary intake of respective foods were clearly confirmed in the KarMeN subset. Conclusions: Overall, the method turned out to be well suited for application in nutrition studies, as shown for the example of food intake biomarkers in KarMeN. Application to a variety of questions such as food‐related effects or physical activity will support future studies in the context of nutrition and health.